Preparation method of carbon steel anti-corrosion composite coating

By modifying SiO2, heat-treated HA-SiO2 is prepared and added to the plating solution, forming a carbon steel composite plating layer with good acid and alkali resistance characteristics, solving the problem of nanotechnology in acidity and alkalinity in the prior art Problem of insufficient corrosion resistance in the environment.

CN119392228AActive Publication Date: 2025-02-07TIANJIN JINGCHENGWEIYE MASCH MFG CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510001441.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-02-07
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

In the prior art, the corrosion resistance of nanotechnology in acidic and alkaline environments still needs to be improved, and it is difficult to meet the high corrosion resistance demand for metal materials in the industrial field.

Method used

By modifying common SiO2, heat-treated HA-SiO2 is prepared and added to the plating solution to form a carbon steel composite coating with good corrosion resistance in an acidic and alkaline environment.

Benefits of technology

It significantly improves the corrosion resistance of SiO2 in acidic environments, and has good acid resistance and alkali resistance, meeting the high corrosion resistance of metal materials in the industrial field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of chemical composite coatings, in particular to a preparation method of a carbon steel anti-corrosion composite coating. The method specifically comprises the following steps that 1, a low-carbon steel sample is mechanically polished; 2, the low-carbon steel sample is deoiled; 3, the low-carbon steel sample is activated; 4, plating the low-carbon steel sample obtained through activation in the step 3 in a plating solution; the plating solution is composed of sodium dodecyl sulfate, nickel sulfate hexahydrate, nickel hypophosphite, citric acid, sodium succinate, heat-treated HA-SiO2 and deionized water. 5, after plating is finished, the low-carbon steel sample is washed with deionized water, then ultrasonic treatment is conducted for 10 min in absolute ethyl alcohol, and then drying is conducted for standby application; and 6, the low-carbon steel sample is subjected to heat treatment for 1 h in a muffle furnace at the temperature of 400 DEG C. According to the invention, common SiO2 is further modified, so that the corrosion resistance of the SiO2 in an acid environment is improved, and meanwhile, the SiO2 has good acid resistance and alkali resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical composite coatings, and in particular to a method for preparing a carbon steel anti-corrosion composite coating. Background Art

[0002] Material corrosion refers to the phenomenon that the performance of materials gradually decreases during the interaction with the environment. In the application of metals, especially in industrial fields such as oil, gas, chemicals, mineral processing, mining and seawater desalination, the performance degradation and corrosion of metal materials are particularly critical. The corrosion and wear of metal materials are one of the main factors leading to the damage of steel components.

[0003] Chemical plating is a process that reduces metal ions in the plating solution to metals through a reducing agent without applying an external current. Chemical composite plating is a method of co-depositing particles and metal ions on the metal surface through chemical plating technology to form a composite material layer. It is an advanced branch of surface treatment technology. The chemical composite plating technology doped with nanoparticles has the advantages of simple equipment, convenient operation, low cost and easy adjustment. This technology can not only enhance the corrosion resistance, wear resistance and oxidation resistance of the metal surface, but also give the material a beautiful appearance and other unique functions. However, the corrosion resistance of some nano technologies still needs to be improved. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a carbon steel anti-corrosion composite coating.

[0005] The present invention is achieved through the following technical solution: A method for preparing a carbon steel anti-corrosion composite coating comprises the following steps: Step 1: Mechanically grind the low carbon steel sample; Step 2: Degreasing the low carbon steel sample; Step 3: Activate the low carbon steel sample; Step 4: Plating the low-carbon steel sample activated in step 3 in a plating solution; The plating solution is composed of sodium dodecyl sulfate, nickel sulfate hexahydrate, nickel hypophosphite, citric acid, sodium succinate, heat-treated HA-SiO2 and deionized water; Step 5: After plating, the low-carbon steel sample was rinsed with deionized water, then ultrasonicated in anhydrous ethanol for 10 min, and then dried for later use; Step 6: Heat treat the low carbon steel sample in a muffle furnace at 400 °C for 1 h.

[0006] In the prior art, different nanomaterials are added to the plating solution to change the corrosion resistance, wear resistance and other properties of the coating. The present application further modifies the common SiO2 to improve its corrosion resistance in an acidic environment, while also having good acid and alkali resistance.

[0007] Furthermore, in step 4, the preparation method of the plating solution is: take 0.1 mg of sodium dodecyl sulfate and add it to 1 L of deionized water, then add 0.5 g to 4.0 g of heat-treated HA-SiO2, ultrasonicate for 10 minutes, and then add 20 g of nickel sulfate hexahydrate, 24 g of nickel hypophosphite, 16 g of citric acid, and 6 g of sodium succinate in sequence, and ultrasonicate for 30 minutes to obtain.

[0008] Furthermore, the added amount of the heat-treated HA-SiO2 is 3.0 g.

[0009] Furthermore, the preparation method of the heat-treated HA-SiO2 is: SiO2 powder is dispersed in 0.6wt% HNO3, stirred for 2h, hydroxyapatite is added, stirred at room temperature for 96h, and then dried at 50°C to obtain HA-SiO2; wherein the mass ratio of SiO2 to hydroxyapatite is 2:3, and the obtained HA-SiO2 is treated at 800°C for 3h to obtain heat-treated HA-SiO2.

[0010] Furthermore, the mechanical grinding method in step 1 is: the low-carbon steel sample is polished with SiC sandpaper of different particle sizes until the surface is smooth, and the low-carbon steel sample is cleaned with deionized water each time the sandpaper is replaced.

[0011] Furthermore, the particle sizes are 100#, 400#, 500#, 800#, 1200#, and 1500# respectively.

[0012] Furthermore, the degreasing method in step 2 is: ultrasonically treating the low carbon steel sample in acetone for 20 minutes, then ultrasonically treating the low carbon steel sample in a 40 g / L NaOH aqueous solution for 20 minutes, and then washing with water.

[0013] Furthermore, the plating method in step 4 is: after rinsing the low-carbon steel sample with deionized water, immediately place it in a plating solution preheated to 85-90°C; stir the plating solution and maintain the plating temperature at 85-90°C.

[0014] Furthermore, the plating time is 2 to 3 hours, preferably 2 hours.

[0015] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention further modifies common SiO2 to improve its corrosion resistance in acidic environment, and at the same time has good acid resistance and alkali resistance. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0017] In the Q235B grade low carbon steel of the present invention, carbon C: ≤0.20%, silicon Si: ≤0.35%, manganese Mn: ≤1.4%, sulfur S: ≤0.045%, and phosphorus P: ≤0.045%.

[0018] In the present invention, SO2 is purchased from Sigma-Aldrich, with an average particle size of 190-250 nm; HA is hydroxyapatite powder purchased from Sigma-Aldrich.

[0019] Example 1

[0020] The matrix sample is Q235B grade low carbon steel, with a size of 10×10×3 mm 3 , the specific steps are as follows: Step 1: Polish the low-carbon steel samples with SiC sandpaper of 100#, 400#, 500#, 800#, 1200#, and 1500# grain sizes until the surface is smooth. Clean the low-carbon steel samples with deionized water each time the sandpaper is changed; Step 2: The mild steel sample was ultrasonicated in acetone for 20 min, then ultrasonicated in 40 g / L NaOH aqueous solution for 20 min, and then washed with water; Step 3: Activate the low carbon steel sample by soaking it in 5wt% HCl for 5 min; Step 4: After rinsing the low-carbon steel sample activated in step 3 with deionized water, immediately place it in a plating solution preheated to 85°C; stir the plating solution and maintain the temperature at 85°C for 2 hours, and observe bubbles in the plating solution; The plating solution consists of sodium dodecyl sulfate, nickel sulfate hexahydrate, nickel hypophosphite, citric acid, sodium succinate, heat-treated HA-SiO2 and deionized water. The preparation method of the plating solution is as follows: 0.1 mg of sodium dodecyl sulfate is added to 1 L of deionized water, then 0.5 g of heat-treated HA-SiO2 is added, ultrasonic treatment is performed for 10 minutes, then 20 g of nickel sulfate hexahydrate, 24 g of nickel hypophosphite, 16 g of citric acid and 6 g of sodium succinate are added in sequence, and ultrasonic treatment is performed for 30 minutes.

[0021] Step 5: After plating, the low-carbon steel sample was rinsed with deionized water, then ultrasonicated in anhydrous ethanol for 10 min, and then dried for later use; Step 6: Heat treat the low carbon steel sample in a muffle furnace at 400 °C for 1 h.

[0022] The preparation method of the heat-treated HA-SiO2 is as follows: SiO2 powder is dispersed in 0.6wt% HNO3, stirred for 2h, hydroxyapatite is added, stirred at room temperature for 96h, and then dried at 50°C to obtain HA-SiO2; wherein the mass ratio of SiO2 to hydroxyapatite is 2:3. The obtained HA-SiO2 is treated at 800°C for 3h to obtain heat-treated HA-SiO2.

[0023] Example 2

[0024] The difference between this embodiment and embodiment 1 is that the composition of the plating solution is different.

[0025] Specifically, the plating solution consists of sodium dodecyl sulfate, nickel sulfate hexahydrate, nickel hypophosphite, citric acid, sodium succinate, heat-treated HA-SiO2 and deionized water; the preparation method of the plating solution is: take 0.1 mg of sodium dodecyl sulfate and add it to 1L of deionized water, then add 1.0g of heat-treated HA-SiO2, ultrasonicate for 10 minutes, then add 20g of nickel sulfate hexahydrate, 24g of nickel hypophosphite, 16g of citric acid, 6g of sodium succinate in sequence, and ultrasonicate for 30 minutes to obtain.

[0026] Example 3

[0027] The difference between this embodiment and embodiment 1 is that the composition of the plating solution is different.

[0028] Specifically, the plating solution consists of sodium dodecyl sulfate, nickel sulfate hexahydrate, nickel hypophosphite, citric acid, sodium succinate, heat-treated HA-SiO2 and deionized water; the preparation method of the plating solution is: take 0.1 mg of sodium dodecyl sulfate and add it to 1L of deionized water, then add 1.5g of heat-treated HA-SiO2, ultrasonicate for 10 minutes, then add 20g of nickel sulfate hexahydrate, 24g of nickel hypophosphite, 16g of citric acid, 6g of sodium succinate in sequence, and ultrasonicate for 30 minutes to obtain.

[0029] Example 4

[0030] The difference between this embodiment and embodiment 1 is that the composition of the plating solution is different.

[0031] Specifically, the plating solution consists of sodium dodecyl sulfate, nickel sulfate hexahydrate, nickel hypophosphite, citric acid, sodium succinate, heat-treated HA-SiO2 and deionized water; the preparation method of the plating solution is: take 0.1 mg of sodium dodecyl sulfate and add it to 1L of deionized water, then add 2.0g of heat-treated HA-SiO2, ultrasonicate for 10 minutes, then add 20g of nickel sulfate hexahydrate, 24g of nickel hypophosphite, 16g of citric acid, 6g of sodium succinate in sequence, and ultrasonicate for 30 minutes to obtain.

[0032] Example 5

[0033] The difference between this embodiment and embodiment 1 is that the composition of the plating solution is different.

[0034] Specifically, the plating solution consists of sodium dodecyl sulfate, nickel sulfate hexahydrate, nickel hypophosphite, citric acid, sodium succinate, heat-treated HA-SiO2 and deionized water; the preparation method of the plating solution is: take 0.1 mg of sodium dodecyl sulfate and add it to 1L of deionized water, then add 3.0g of heat-treated HA-SiO2, ultrasonicate for 10 minutes, and then add 20g of nickel sulfate hexahydrate, 24g of nickel hypophosphite, 16g of citric acid, 6g of sodium succinate in sequence, and ultrasonicate for 30 minutes to obtain.

[0035] Example 6

[0036] The difference between this embodiment and embodiment 1 is that the composition of the plating solution is different.

[0037] Specifically, the plating solution consists of sodium dodecyl sulfate, nickel sulfate hexahydrate, nickel hypophosphite, citric acid, sodium succinate, heat-treated HA-SiO2 and deionized water; the preparation method of the plating solution is: take 0.1 mg of sodium dodecyl sulfate and add it to 1L of deionized water, then add 4.0g of heat-treated HA-SiO2, ultrasonicate for 10 minutes, then add 20g of nickel sulfate hexahydrate, 24g of nickel hypophosphite, 16g of citric acid, 6g of sodium succinate in sequence, and ultrasonicate for 30 minutes to obtain.

[0038] Comparative Example 1 The matrix sample is Q235B grade low carbon steel, with a size of 10×10×3 mm 3 , the specific steps are as follows: Step 1: Polish the low-carbon steel samples with SiC sandpaper of 100#, 400#, 500#, 800#, 1200#, and 1500# grain sizes until the surface is smooth. Clean the low-carbon steel samples with deionized water each time the sandpaper is changed; Step 2: The mild steel sample was ultrasonicated in acetone for 20 min, then ultrasonicated in 40 g / L NaOH aqueous solution for 20 min, and then washed with water; Step 3: Activate the low carbon steel sample by soaking it in 5wt% HCl for 5 min; Step 4: After rinsing the low-carbon steel sample activated in step 3 with deionized water, immediately place it in a plating solution preheated to 85°C; stir the plating solution and maintain the temperature at 85°C for 2 hours, and observe bubbles in the plating solution; The plating solution consists of sodium dodecyl sulfate, nickel sulfate hexahydrate, nickel hypophosphite, citric acid, sodium succinate, HA-SiO2 and deionized water. The preparation method of the plating solution is as follows: 0.1 mg of sodium dodecyl sulfate is added to 1 L of deionized water, then 1.0 g of HA-SiO2 is added, ultrasonic treatment is performed for 10 minutes, then 20 g of nickel sulfate hexahydrate, 24 g of nickel hypophosphite, 16 g of citric acid and 6 g of sodium succinate are added in sequence, and ultrasonic treatment is performed for 30 minutes.

[0039] Step 5: After plating, the low-carbon steel sample was rinsed with deionized water, then ultrasonicated in anhydrous ethanol for 10 min, and then dried for later use; Step 6: Heat treat the low carbon steel sample in a muffle furnace at 400 °C for 1 h.

[0040] The preparation method of the heat-treated HA-SiO2 is as follows: SiO2 powder is dispersed in 0.6wt% HNO3, stirred for 2h, hydroxyapatite is added, stirred at room temperature for 96h, and then dried at 50°C to obtain HA-SiO2; wherein the mass ratio of SiO2 to hydroxyapatite is 2:3.

[0041] Comparative Example 2 The difference between this comparative example and comparative example 1 is that the composition of the plating solution is different.

[0042] The plating solution consists of sodium dodecyl sulfate, nickel sulfate hexahydrate, nickel hypophosphite, citric acid, sodium succinate, HA-SiO2 and deionized water. The preparation method of the plating solution is as follows: 0.1 mg of sodium dodecyl sulfate is added to 1 L of deionized water, then 2.0 g of HA-SiO2 is added, ultrasonic treatment is performed for 10 minutes, then 20 g of nickel sulfate hexahydrate, 24 g of nickel hypophosphite, 16 g of citric acid and 6 g of sodium succinate are added in sequence, and ultrasonic treatment is performed for 30 minutes.

[0043] Comparative Example 3 The difference between this comparative example and comparative example 1 is that the composition of the plating solution is different.

[0044] The plating solution consists of sodium dodecyl sulfate, nickel sulfate hexahydrate, nickel hypophosphite, citric acid, sodium succinate, HA-SiO2 and deionized water. The preparation method of the plating solution is as follows: 0.1 mg of sodium dodecyl sulfate is added to 1 L of deionized water, then 3.0 g of HA-SiO2 is added, ultrasonic treatment is performed for 10 minutes, then 20 g of nickel sulfate hexahydrate, 24 g of nickel hypophosphite, 16 g of citric acid and 6 g of sodium succinate are added in sequence, and ultrasonic treatment is performed for 30 minutes.

[0045] Test Example 1 The samples prepared in each embodiment and comparative example were immersed in 15% HCl and 15% NaOH for 240 hours, respectively, and the mass changes of the samples before and after immersion were compared to reflect the acid and alkali resistance. Each measurement was performed three times, and the average value was taken. The ambient temperature was 25°C. The test results are shown in Table 1.

[0046] Table 1 Acid and alkali resistance test

[0047] It can be seen from Table 1 that when heat-treated HA-SiO2 is used in the plating solution, the performance is better than that of HA-SiO2 without heat treatment in the acid resistance test, while the performance of the two in an alkaline environment is not much different.

[0048] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a carbon steel anti-corrosion composite coating, characterized in that: The following steps are involved: Step 1: Mechanically grind the low carbon steel sample; Step 2: Degreasing the low carbon steel sample; Step 3: Activate the low carbon steel sample; Step 4: Plating the low-carbon steel sample activated in step 3 in a plating solution; The plating solution is composed of sodium dodecyl sulfate, nickel sulfate hexahydrate, nickel hypophosphite, citric acid, sodium succinate, heat-treated HA-SiO2 and deionized water; Step 5: After plating, the low-carbon steel sample was rinsed with deionized water, then ultrasonicated in anhydrous ethanol for 10 min, and then dried for later use; Step 6: Heat treat the low carbon steel sample in a muffle furnace at 400 °C for 1 h.

2. The method for preparing the carbon steel anti-corrosion composite coating according to claim 1, characterized in that: In step 4, the preparation method of the plating solution is: take 0.1 mg of sodium dodecyl sulfate and add it to 1 L of deionized water, then add 0.5 g to 4.0 g of heat-treated HA-SiO2, ultrasonicate for 10 minutes, and then add 20 g of nickel sulfate hexahydrate, 24 g of nickel hypophosphite, 16 g of citric acid, and 6 g of sodium succinate in sequence, and ultrasonicate for 30 minutes to obtain.

3. The method for preparing the carbon steel anti-corrosion composite coating according to claim 2, characterized in that: The added amount of the heat-treated HA-SiO2 is 3.0 g.

4. The method for preparing the carbon steel anti-corrosion composite coating according to claim 1, characterized in that: The preparation method of the heat-treated HA-SiO2 is as follows: SiO2 powder is dispersed in 0.6wt% HNO3, stirred for 2h, hydroxyapatite is added, stirred at room temperature for 96h, and then dried at 50°C to obtain HA-SiO2; wherein the mass ratio of SiO2 to hydroxyapatite is 2:3, and the obtained HA-SiO2 is treated at 800°C for 3h to obtain heat-treated HA-SiO2.

5. The method for preparing the carbon steel anti-corrosion composite coating according to claim 1, characterized in that: The mechanical grinding method in step 1 is: the low-carbon steel sample is polished with SiC sandpaper of different particle sizes until the surface is smooth, and the low-carbon steel sample is cleaned with deionized water each time the sandpaper is replaced.

6. The method for preparing the carbon steel anti-corrosion composite coating according to claim 5, characterized in that: The particle sizes are 100#, 400#, 500#, 800#, 1200# and 1500# respectively.

7. The method for preparing the carbon steel anti-corrosion composite coating according to claim 1, characterized in that: The degreasing method in step 2 is: ultrasonically treat the low carbon steel sample in acetone for 20 minutes, then ultrasonically treat the sample in a 40 g / L NaOH aqueous solution for 20 minutes, and then wash the sample with water.

8. The method for preparing the carbon steel anti-corrosion composite coating according to claim 1, characterized in that: The plating method in step 4 is: after rinsing the low-carbon steel sample with deionized water, immediately place it in a plating solution preheated to 85-90° C.; stir the plating solution and maintain the plating temperature at 85-90° C.

9. The method for preparing the carbon steel anti-corrosion composite coating according to claim 8, characterized in that: The plating time is 2 to 3 hours.

10. The method for preparing the carbon steel anti-corrosion composite coating according to claim 9, characterized in that: The plating time is 2h.

Citation Information

Patent Citations

  • Method for enhancing nickel-phosphorus composite deposit by using modified nano silicon dioxide particles

    CN101906625A

  • Preparation method of silica particle reinforced nickel-base composite coating for conducting rolls

    CN103031585A

  • Electrochemical method for preparation of silicon-containing hydroxyapatite nano composite coating on nickel titanium alloy surface

    CN103726089A

  • Anticorrosive fireproof coating specially used for steel structures and preparation method thereof

    CN107163815A

  • Preparation method of anti-corrosion wood with surface uniformly and chemically plated with Ni-P-SiO2 nano-particle composite layer

    CN110158065A